Social research with children and young people : a practical guide / Louca-Mai Brady, Berni Graham. - Brady, Louca-Mai; Graham, Berni (Policy Press shorts. Policy & practice., 2019)
This book provides a practical and concise introductory guide to doing research with children and young people, outlining the benefits and challenges along with key ethical, methodological and other considerations. Throughout, there are practical examples, checklists and top tips to aid the reader.